2018
DOI: 10.1111/tpj.14011
|View full text |Cite
|
Sign up to set email alerts
|

Role of GhHDA5 in H3K9 deacetylation and fiber initiation in Gossypium hirsutum

Abstract: Cotton fibers are single-celled trichomes that initiate from the epidermal cells of the ovules at or before anthesis. Here, we identified that the histone deacetylase (HDAC) activity is essential for proper cotton fiber initiation. We further identified 15 HDACs homoeologs in each of the A- and D-subgenomes of Gossypium hirsutum. Few of these HDAC homoeologs expressed preferentially during the early stages of fiber development [-1, 0 and 6 days post-anthesis (DPA)]. Among them, GhHDA5 expressed significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 68 publications
(94 reference statements)
1
57
0
Order By: Relevance
“…Within the superfamily of HDACs, the RPD3 gene family is the most studied and is crucial in plant development and physiological processes, including flowering time, abiotic stress response, female gametophyte and embryo development, senescence, seed germination, and plant hormone signal response [12-14, 19, 26-28]. To date, although a few studies have analyzed the function of the RPD3 family members in G. hirsutum, they focus primarily on the roles of GhHDA5 in fiber initiation, and there are no systematic reports [29]. To explore the characteristics of RPD3 family members and understand the roles played by cotton RPD3 genes in cotton growth and development, we conducted an integrated analysis of the RPD3 gene family in cotton, containing their phylogenetic relationships, exon-intron structures, conserved motifs, chromosomal distributions, duplication events, expression patterns in different tissues and in the presence of abiotic stresses or MeJA and ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the superfamily of HDACs, the RPD3 gene family is the most studied and is crucial in plant development and physiological processes, including flowering time, abiotic stress response, female gametophyte and embryo development, senescence, seed germination, and plant hormone signal response [12-14, 19, 26-28]. To date, although a few studies have analyzed the function of the RPD3 family members in G. hirsutum, they focus primarily on the roles of GhHDA5 in fiber initiation, and there are no systematic reports [29]. To explore the characteristics of RPD3 family members and understand the roles played by cotton RPD3 genes in cotton growth and development, we conducted an integrated analysis of the RPD3 gene family in cotton, containing their phylogenetic relationships, exon-intron structures, conserved motifs, chromosomal distributions, duplication events, expression patterns in different tissues and in the presence of abiotic stresses or MeJA and ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In short days, AtHDA9 represses the flowering-promoting gene AGL19 (AGAMOUS-LIKE 19) regulated by photoperiod [35] and the downregulation of AtHDA19 causes delayed flowering, flower abnormalities, embryonic defects, and seed set reduction [36]. In recent studies, GhHDA5, similar to AtHDA5 in Arabidopsis, exhibited higher expression at − 1 and 0 DPA, and RNAirepressed GhHDA5 lines showed delayed flowering, suggesting that it may be involved in cotton fiber initiation and flowering time [29]. As the homologous genes of these four AtRPD3 genes related to flowering time in cotton, the gene pairs GhHDA2/GhHDA13, homologous to AtHDA6, and GhHDA6/GhHDA15, homologous to AtHDA9, showed markedly higher expression in earlymaturity cotton compare with late-maturity cotton during all five stages of flower bud differentiation.…”
Section: Functional Analysis Of Ghrpd3 Genes In Upland Cottonmentioning
confidence: 99%
“…GhHDA5 RNAi lines changed the ROS homeostasis and elevated autophagic cell death, which, in turn, decreased fibre initiation and lint yield. ChIP‐PCR showed that H3K9 acetylation level on some associated downstream genes regulated by GhHDA5 was up‐regulated in the RNAi lines (Kumar et al ., ). HISTONE MONOUBIQUITINATION2 (HUB2) encoding histone H2B monoubiquitination E3 ligase was shown to have a role in fibre elongation and SCW deposition in transgenic cotton.…”
Section: The Mechanisms Of Epigenetic Modifications In Cotton Fibre Dmentioning
confidence: 97%
“…Within the superfamily of HDACs, the RPD3 gene family is the most studied and is crucial in plant development and physiological processes, including owering time, abiotic stress response, female gametophyte and embryo development, senescence, seed germination, and plant hormone signal response [12-14, 19, 26-28]. To date, although a few studies have analyzed the function of the RPD3 family members in G. hirsutum, they focus primarily on the roles of GhHDA5 in ber initiation, and there are no systematic reports [29]. To explore the characteristics of RPD3 family members and understand the roles played by cotton RPD3 genes in cotton growth and development, we conducted an integrated analysis of the RPD3 gene family in cotton, containing their phylogenetic relationships, exon-intron structures, conserved motifs, chromosomal distributions, duplication events, expression patterns in different tissues and in the presence of abiotic stresses or MeJA and ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In short days, AtHDA9 represses the owering-promoting gene AGL19 (AGAMOUS-LIKE 19) regulated by photoperiod [35] and the downregulation of AtHDA19 causes delayed owering, ower abnormalities, embryonic defects, and seed set reduction [36]. In recent studies, GhHDA5, similar to AtHDA5 in Arabidopsis, exhibited higher expression at -1 and 0 DPA, and RNAi-repressed GhHDA5 lines showed delayed owering, suggesting that it may be involved in cotton ber initiation and owering time [29]. As the homologous genes of these four AtRPD3 genes related to owering time in cotton, the gene pairs GhHDA2/GhHDA13, homologous to AtHDA6, and GhHDA6/GhHDA15, homologous to AtHDA9, showed markedly higher expression in early-maturity cotton compare with late-maturity cotton during all ve stages of ower bud differentiation.…”
Section: Functional Analysis Of Ghrpd3 Genes In Upland Cottonmentioning
confidence: 99%